Exacerbation of inflammatory disseminated superficial porokeratosis following COVID‐19 vaccination - Tomomu Ishikawa; Jun Asai; Norito katoh (Wiley, 2023)
Abstract The mRNA‐1273 vaccine for coronavirus disease (COVID‐19) authorised as one of the first COVID‐19 vaccines was released by Moderna in December 2020. A recent study indicates that messenger RNA (mRNA) vaccines appear to be effective in preventing aggravation, hospitalisation and death against COVID‐19 infection. However several adverse effects have been reported. Of these, the dermatological adverse effects are relatively rare entities Herein, we present a case of inflammatory disseminated superficial porokeratosis exacerbated after administration of the fourth dose of the mRNA‐1273 vaccine.